Objective shade matching, communication, and reproduction by combining dental photography and numeric shade quantification - Hein, Sascha; Modrić, Danijela; Westland, Stephen; Tomeček, Martin (Journal of esthetic and restorative dentistry, 2021)
OBJECTIVE: The subject of this case report is the application of a newly developed workflow for objective shade communication sans visual shade assessment or the use of shade guides. CLINICAL CONSIDERATIONS: Clinical complications stemming from issues relating to esthetic integration can present a burden on the restorative team, often resulting in strenuous relationships among its members. The faithful imitation of the optical appearance of dental hard tissues with direct- and indirect restorations has been at the center of interest in a great number of publications from the realm of esthetic dentistry over the past 40 years. The present report describes a new approach to objective shade communication, by transcending the role of dental photography from its purely descriptive purpose to the level of quantification, thus abandoning the use of the established shading regimes and replacing them with a patient personal shade recipe based on the CIELAB color space instead. CONCLUSIONS: Objective shade communication is possible with the eLAB system by combining numeric shade quantification with dental photography. CLINICAL SIGNIFICANCE: The eLAB system presents a viable alternative to the traditional approach to shade communication and shade matching in dentistry.
Keywords: rozmnožování; shade matching; Reproduction; zubní protéza - design; barvení protéz; Dental Prosthesis Design; Photography, Dental; Prosthesis Coloring; dental photography; shade communication; Communication; Color; lidé; dental ceramics; Humans; komunikace; fotografie zubní; barva